Current scientific evidence for a polarized cardiovascular endurance training model - Hydren, J. R.; Cohen, B. S. (The Journal of Strength and Conditioning Research, 2015)
Recent publications have provided new scientific evidence for a modern aerobic or cardiovascular endurance exercise prescription that optimizes the periodization cycle and maximizes potential endurance performance gains in highly trained individuals. The traditional threshold, high volume, and high-intensity training models have displayed limited improvement in actual race pace in (highly) trained individuals while frequently resulting in overreaching or overtraining (physical injury and psychological burnout). A review of evidence for replacing these models with the proven polarized training model seems warranted. This review provides a short history of the training models, summarizes 5 key studies, and provides example training programs for both the pre- and in-season periods. A polarized training program is characterized by an undulating nonlinear periodization model with nearly all the training time spent at a "light" (=13) and "very hard" (=17) pace with very limited time at "hard" (14-16) or race pace (6-20 Rating of Perceived Exertion [RPE] scale). To accomplish this, the polarization training model has specific high-intensity workouts separated by one or more long slow distance workouts, with the exercise intensity remaining below ventilatory threshold (VT) 1 and/or blood lactate of less than 2 mM (A.K.A. below race pace). Effect sizes for increasing aerobic endurance performance for the polarized training model are consistently superior to that of the threshold training model. Performing a polarized training program may be best accomplished by: going easy on long slow distance workouts, avoiding "race pace" and getting after it during interval workouts.